Transcryptomic Analysis of Human Brain -Microvascular Endothelial Cell Driven Changes in -Vascular Pericytes - Kurmann, Lisa (Cells, 2021)
Many pathological conditions of the brain are associated with structural abnormalities within the neurovascular system and linked to pericyte (PC) loss and/or dysfunction. Since crosstalk between endothelial cells (ECs) and PCs greatly impacts the function of the blood–brain barrier (BBB), effects of PCs on endothelial integrity and function have been investigated extensively. However, the impact of ECs on the function and activity of PCs remains largely unknown. Hence, using co-cultures of human brain vascular PCs with human cerebral microvascular ECs on opposite sides of porous Transwell inserts which facilitates direct EC–PC contact and improves EC barrier function, we analyzed EC-driven transcriptomic changes in PCs using microarrays and changes in cytokines/chemokines using proteome arrays. Gene expression analysis (GEA) in PCs co-cultured with ECs versus PCs cultured alone showed significant upregulation of 1′334 genes and downregulation of 964 genes. GEA in co-cultured PCs revealed increased expression of five prominent PC markers as well as soluble factors, such as transforming growth factor beta, fibroblast growth factor, angiopoietin 1, brain-derived neurotrophic factor, all of which are involved in EC–PC crosstalk and BBB induction. Pathway enrichment analysis of modulated genes showed a strong impact on many inflammatory and extracellular matrix (ECM) pathways including interferon and interleukin signaling, TGF-β and interleukin-1 regulation of ECM, as well as on the mRNA processing pathway. Interestingly, while co-culture induced the mRNA expression of many chemokines and cytokines, including several CCL- and CXC-motif ligands and interleukins, we observed a decreased expression of the same inflammatory mediators on the protein level. Importantly, in PCs, ECs significantly induced interferon associated proteins (IFIT1, IFI44L, IF127, IFIT3, IFI6, IFI44) with anti-viral actions; downregulated prostaglandin E receptor 2 (prevent COX-2 mediated BBB damage); upregulated fibulin-3 and connective tissue growth factor essential for BBB integrity; and multiple ECMs (collagens and integrins) that inhibit cell migration. Our findings suggest that via direct contact, ECs prime PCs to induce molecules to promote BBB integrity and cell survival during infection and inflammatory insult. Taken together, we provide first evidence that interaction with ECs though porous membranes induces major changes in the transcriptomic and proteomic profile of PCs. ECs influence genes involved in diverse aspects of PC function including PC maturation, cell survival, anti-viral defense, blood flow regulation, immuno-modulation and ECM deposition.